Search for Novel Diagnostic Biomarkers of Prostate Inflammation-Related Disorders: Role of Transglutaminase Isoforms as Potential Candidates - Maria Pia Savoca; Antonino Inferrera; Elisabetta A. M. Verderio; Daniela Caccamo (Mediators of Inflammation)
Investigations on prostate inflammation-related disorders, including acute and chronic prostatitis, chronic pelvic pain syndrome, benign prostate hyperplasia (BPH), and prostate cancer (PCa), are still ongoing to find new, accurate, and noninvasive biomarkers for a differential diagnosis of those pathological conditions sharing some common macroscopic features. Moreover, an ideal biomarker should be useful for risk assessment of prostate inflammation progression to more severe disorders, like BPH or PCa, as well as for monitoring of treatment response and prognosis establishment in carcinoma cases. Recent literature evidence highlighted that changes in the expression of transglutaminases, enzymes that catalyze transamidation reactions leading to posttranslational modifications of soluble proteins, occur in prostate inflammation-related disorders. This review focuses on the role specifically played by transglutaminases 4 (TG4) and 2 (TG2) and suggests that both isoenzymes hold a potential to be included in the list of candidates as novel diagnostic biomarkers for the above-cited prostate pathological conditions.